Das soluções sem conflito aos conflitos sem solução: a questão Palestina: um enfoque sistêmico-funcional - Beo, Tatiana Di (2024)
The 20th century saw the emergence of conditions in which the lives of Jews and Palestinian Arabs, intertwined for millennia and in peaceful coexistence for a long time, resulted, in the 21st century, in a context of extreme violence, the consequences of which for the world are yet to come. On October 7, 2023, an operation carried out by the Hamas organization against Israeli targets and actions in retaliation carried out by the State of Israel against Palestine, broke out in different media, showing the horror of brutal impacts, even victimizing civilian populations. If we are ever to emerge from this conflict, perhaps the way forward will begin with finding a language that allows us to describe it. However, if on the one hand language seems insufficient to describe the tragedy, on the other it is important to investigate how discursive constructions work to persuade the reader about a given event. Language imprints interpretations of reality that can seduce, convince and influence public opinion. Critical discourse analysis is interested in questioning the relationships between sign, meaning and the socio-historical context that govern the semiotic structure of discourse, using a type of linguistic analysis. By studying details of the linguistic structure in the light of the social and historical situation of a text, it seeks to bring to the level of consciousness the patterns of beliefs and values encoded in the language - which underlie the news, and which are invisible to those who accept discourse as something "natural". The aim of this master's dissertation is to examine the possibility of a solution, or not, to the Israeli-Palestinian conflict announced in two opinion articles. To this end, the opinion articles by Clemesha et al and Demétrio Magnoli, published in the Folha de São Paulo newspaper after October 7, were initially examined. The authors point to what they consider to be the reasons for the war and, to some extent, also, their perspectives regarding the possibility of achieving the conditions for negotiating peace. The analysis of the articles, however, made it possible to assess, at least to conclude from the two articles, that the reasons put into question by both texts to put an end to the conflict are subject to conditions that are difficult to achieve given the reality that currently exists. This dissertation leads me to examine the possibilities of better understanding this conflict, a more grounded understanding of the reasons for its development. This study is supported by Systemic-Functional Linguistics, Critical Linguistics and rhetorical resources of persuasion. The research answers the following questions: (a) How are opinion articles about the Israeli-Palestinian conflict expressed? What are the main reasons put forward?